2017
DOI: 10.1155/2017/5965492
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intereukin-31 in Pathogenesis of Itch and Its Intensity in a Course of Bullous Pemphigoid and Dermatitis Herpetiformis

Abstract: Itch which is one of the major, subjective symptoms in a course of bullous pemphigoid and dermatitis herpetiformis makes those two diseases totally different than other autoimmune blistering diseases. Its pathogenesis is still not fully known. The aim of this research was to assess the role of IL-31 in development of itch as well as to measure its intensity. Obtained results, as well as literature data, show that lower concentration of IL-31 in patients' serum may be correlated with its role in JAK/STAT signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
4
23
1
Order By: Relevance
“…It is, however, as yet unclear whether BP patients display elevated serum levels of IL-31, since the currently published literature has reported conflicting observations. Our own investigation showed only minor elevations in serum IL-31 levels vs. non-BP controls (51) compared to Salz et al (50), who observed significant increases, and Kulczycka-Siennicka et al (52), who reported reduced levels of the cytokine. Despite these different observations regarding IL-31 serum levels, it is clear that eosinophils are one of the major sources for the increased IL-31 levels in BP blister fluids, which often contain a highly enriched accumulation of eosinophils.…”
Section: Il-31 In Autoimmune Skin Diseasescontrasting
confidence: 46%
“…It is, however, as yet unclear whether BP patients display elevated serum levels of IL-31, since the currently published literature has reported conflicting observations. Our own investigation showed only minor elevations in serum IL-31 levels vs. non-BP controls (51) compared to Salz et al (50), who observed significant increases, and Kulczycka-Siennicka et al (52), who reported reduced levels of the cytokine. Despite these different observations regarding IL-31 serum levels, it is clear that eosinophils are one of the major sources for the increased IL-31 levels in BP blister fluids, which often contain a highly enriched accumulation of eosinophils.…”
Section: Il-31 In Autoimmune Skin Diseasescontrasting
confidence: 46%
“…At present there are conflicting reports regarding relative IL-31 levels in BP sera compared with healthy controls. Kulczycka-Siennicka et al (29) reported reduced levels of IL-31 in BP sera, whereas a recent study by Salz et al (30), which was published at the time our current work was first submitted, reported significant increases. Salz et al (30) also observed high levels of IL-31 in BP blister fluids, as well as an association with granulocytes (30), which we can confirm, although our study demonstrates for the first time that eosinophils are the main source of this cytokine.…”
Section: Discussionmentioning
confidence: 56%
“…We have previously shown that Th2 type cytokines are also elevated in the skin of DH patients, thereby allowing speculation about a possible role of IL-31 in the associated pruritus. Interestingly, while a previous paper did not show significant elevation of serum IL-31 concentration in DH patients (152), a recent study by our group demonstrated that IL-31 was not only elevated in DH serum, but also significantly over-expressed in the skin, where it co-localized with IL-31RA (153).…”
Section: Pathogenesismentioning
confidence: 57%